Pendugaan Fungsi Keuntungan dan Skala Usaha Budidaya Pembesaran Ikan Bandeng di Kecamatan Palang Kabupaten Tuban Jawa Timur - Tajerin Tajerin; Mohammad Noor (Universitas Islam Indonesia, 2003)
The Chanos chanos Forsk fish culture, at the present time has been growing and made important role in economic. This paper purposed to examine factors affected on the profit rate earned form Chanos chanos Forsk fish cultured, achievements of the short run profit maximization, and conducted resulted from the culture’s return to scale. The research was conducted in Palang Sub District Tuban District, South Java during July to September 2003. The area sample was selected by purposively and the respondent of fish farmer was selected by stratified random sampling. The result of study show that simultaneously the fish seed, feed seed, human labor, culture area wide and investment capitals were affected the profit earned for fish farmers with highly significant levels. Result was also indicate that the farms in location research were hardly provide the maximum profit and the return to scale was calculated to be increased. Considered with the phenomena’s, the development of Chanos chanos Forsk fish culture in Palang Sub District Tuban District, Shout Java suggested to be done by culture intensive method.Keywords: Profit Function, Return to Scale, Chanos chanos Forsk